Polycrystalline Formamidinium Lead Bromide X-ray Detectors - Suad Alghamdi; Stephanie Bennett; Carol Crean; Joydip Ghosh; Harry Gibbard; Robert Moss; Justin Reiss; Douglas Wolfe; Paul Sellin (Applied Sciences, 2022)
We have investigated the performance of formamidinium lead bromide (FAPbBr<semantics>3</semantics>) perovskite X-ray detectors fabricated from polycrystalline material that is pressed into a pellet at high pressures. FAPbBr<semantics>3</semantics> has been shown to exhibit a remarkable combination of electrical and physical properties, such that mechanically-formed polycrystalline pellets exhibit good charge transport properties suitable for use as X-ray detectors. We characterise the morphology and structure of FAPbBr<semantics>3</semantics> pellets using photoluminescence (PL), electron microscopy (SEM) and X-ray diffraction (XRD), and demonstrate an improvement in the microstructure, density, and charge transport performance of the material as the pressure is increased from 12 MPa to 124 MPa. The use of annealing of the pellets after pressing also improves the stability and charge transport performance of the devices. Using a 40 kV X-ray beam, a maximum X-ray sensitivity of 169 µC Gy<semantics>−1</semantics> cm<semantics>−2</semantics> was measured, and the fast time response of the devices was demonstrated using a chopped X-ray beam.